Quality of life and healthcare costs of patients with allergic respiratory diseases: a cross-sectional study - Vivienne Hillerich; Frederik Valbert; Silke Neusser; Oliver Pfaar; Ludger Klimek; Annette Sperl; Thomas Werfel; Eckard Hamelmann; Cordula Riederer; Stefanie Wobbe-Ribinski; Anja Neumann; Jürgen Wasem; et al. (The European Journal of Health Economics, 2023)
Background: Allergic rhinitis (AR) and allergic asthma (AA) are chronic respiratory diseases that represent a global health problem. One aim of this study was to analyze the Health-related Quality of Life (HRQoL) of the patients in order to identify statistically significant influencing factors that determine HRQoL. Another aim was to assess and analyze data on cost-of-illness from a statutory health insurance perspective. Methods: ~The EQ-5D-5L was used to evaluate the patients' HRQoL. To identify the factors influencing the HRQoL, a multinomial logistic regression analysis was conducted using groups based on the EQ-5D-5L index value as dependent variable. Routine data were analyzed to determine total healthcare costs.Results: ~The average EQ-5D-5L index was 0.85 (SD 0.20). A high age, the amount of disease costs, low internal health-related control beliefs and high ozone exposure in the residential area were found to be statistically significant influencing factors for a low HRQoL, whereas low age, male sex and a good possibility to avoid the allergens were found to be statistically significant factors influencing a high HRQoL. On average, the study participants incurred annual costs of exteuro3072 (SD: 3485), of which exteuro699 (SD: 743) could be assigned to allergic respiratory diseases. Conclusions: ~Overall, the patients in the VerSITA study showed a high level of HRQoL. The identified influencing factors can be used as starting points for improving the HRQoL of patients with allergic respiratory diseases. From the perspective of a statutory health insurance, per person expenditures for allergic respiratory diseases are rather low.
Keywords: I10; I13; I18; I19; 610; Asthma; Rhinitis; Health Economics; Health-Related Quality of Life; Healthcare Costs